Post–Electroconvulsive Therapy Recovery and Reorientation Time With Methohexital and Ketamine: A Randomized, Longitudinal, Crossover Design Trial. Issue 1 (March 2015) - Yen, Tony; Khafaja, Mohamad; Lam, Nicholas; Crumbacher, James; Schrader, Ronald; Rask, John; Billstrand, Mary; Rothfork, Jacob; Abbott, Christopher C.
Abstract : Objectives: Methohexital, a barbiturate anesthetic commonly used for electroconvulsive therapy (ECT), possesses dose-dependent anticonvulsant properties, and its use can interfere with effective seizure therapy in patients with high seizure thresholds. Ketamine, an N -methyl-d-aspartate antagonist with epileptogenic properties not broadly used for ECT inductions, is a commonly used induction agent for general anesthesia. Recent studies suggest that the use of ketamine is effective in allowing successful ECT treatment in patients with high seizure thresholds without an increase in adverse effects. In this preliminary study, we directly compared the recovery and reorientation times of subjects receiving ketamine and methohexital for ECTs. Methods: Twenty patients were randomized in a crossover design to receive methohexital and ketamine for ECT inductions in alternating fashion in 6 trials. Primary outcome measures were recovery time (voluntary movement, respiratory effort, blood pressure, consciousness, and O2 saturation) and reorientation time. Secondary outcome measures were individual recovery variables, adverse effect occurrence, and seizure duration. Results: Overall recovery time was not significantly different between the 2 treatment arms (F(1, 17) = 0.72; P = 0.41). Reorientation time was faster in the methohexital arm (F(1, 17) = 9.23; P = 0.007). Conclusion: Ketamine inductions resulted in higher number of adverse effects, higher subject dropout rates, and a longer reorientation time with respect to methohexital inductions. No significant difference in postanesthesia recovery time was found between the ketamine and methohexital arms. Intolerability to ketamine affected a significant proportion of subjects and suggests that ketamine should remain as an alternative or adjunctive agent for patients with high seizure thresholds.